Relationship Between Women’s Empowerment and Having ‘Final Say’ in Household Decision Making Among Ijesa Women of South Western Nigeria - Kolawole, Alonge Sunday (Advances in Social Sciences Research Journal, 2017)
Empowerment of women refers to giving decision-making power to women in social, economic, and political sphere of life. It is a process of making women aware of socio-psycho-cultural and political injustice that is prevailing in the society against women. Having a greater say in household decisions enables women to influence not only their own psychological and physical wellbeing, but also that of their children. This paper examined the relationship between women’s empowerment and having a say or final say in household decision making among Ijesa women of south-western Nigeria. Examining who has a say or final say is important to household quality of life and welfare. A cross-sectional survey design using quantitative technique was employed. A multistage sampling techniqueinvolvingarandom selection of 1,594 ever-married women of childbearing age was carried out. A structured questionnaire was used to collect data. The data wasanalysed using descriptive statistics, bivariate analysis of Chi square, and logistic regression.The findings show that issues relating to number of children to have, the school to send children to, when to buy and sell land, whether or not to use a contraceptive method to avoid getting pregnant, when to have sex, as well as the person to take responsibility for upkeep and rearing of children are mostly jointly decided by husband and wife. The P value of the Chi Square and the Logistic Regression shows that there is significant relationship between women’s empowerment and house hold decisions considered in the study. The study concludes that women who are empowered have final say on the issues under consideration, compared to their counterparts who are not empowered. There is the need therefore for the empowerment of women to achieve better quality of life for household members.